Configuration Design and Performance Analysis of Inter-axle Limited Slip Differential with Face Gears - Peng Xianlong; Wu Guichen (Jixie chuandong)
In order to solve the problems of limited slip limiting ability, complex configuration and difficult manufacturing of inter-axle limited slip differentials, a new design scheme of inter-axle limited slip differentials with face gears is proposed. By analyzing the configuration principle and motion characteristics of the differential, the mechanical balance equation and locking coefficient theoretical model of the differential are established. Based on the machining principle of face gears and the working characteristics of differentials, the 3D entity model and Adams virtual prototype are built. The multi-body dynamics is analyzed by Adams simulation software. The results show that the locking ratio of differentials to the front and rear axles can reach 6.5 and 5. When travelling on a good road, the output torque of the front and rear axles is basically consistent with the preset torque distribution ratio of 40∶60. When travelling on the double-adhesion-coefficient road surface, the slipping axle can be locked quickly, more torque can be distributed to the non-slipping axle, and the torque distribution to the front and rear axles can reach 73% and 79% respectively. The results verify the feasibility of the inter-axle limited slip differential with face gears, and provide a basis for its design and application.